Gastric metastasis of breast cancer: A frequent mimicker of primary gastric cancer in breast cancer patients. Issue 11 (5th October 2022) - van Bekkum, Sara; Menke‐Pluijmers, Marian B E; Westenend, Pieter J
Abstract : Gastric metastasis of breast cancer is a known mimicker of primary gastric cancer. This paper demonstrates that in patients with a history of breast cancer, gastric metastasis and primary gastric cancer are equally likely.